Aberrant functional network recruitment of posterior parietal cortex in turner syndrome. Issue 12 (19th June 2012) - Bray, Signe; Hoeft, Fumiko; Hong, David S.; Reiss, Allan L.
<x xml:space="preserve">Abstract</x> Turner syndrome is a genetic disorder caused by the complete or partial absence of an X chromosome in affected women. Individuals with TS show characteristic difficulties with executive functions, visual‐spatial and mathematical cognition, with relatively intact verbal skills, and congruent abnormalities in structural development of the posterior parietal cortex (PPC). The functionally heterogeneous PPC has recently been investigated using connectivity‐based clustering methods, which sub‐divide a given region into clusters of voxels showing similar structural or functional connectivity to other brain regions. In the present study, we extended this method to compare connectivity‐based clustering between groups and investigate whether functional networks differentially recruit the PPC in TS. To this end, we parcellated the PPC into sub‐regions based on temporal correlations with other regions of the brain. fMRI data were collected from 15 girls with TS and 14 typically developing (TD) girls, aged 7–14, while they performed a visual‐spatial task. Temporal correlations between voxels in the PPC and a set of seed regions were calculated, and the PPC divided into clusters of voxels showing similar connectivity. It was found that in general the PPC parcellates similarly in TS and TD girls, but that regions in bilateral inferior parietal lobules, and posterior right superior parietal lobule, were reliably recruited by different networks in TS relative to TD participants. These regions showed weaker correlation in TS with a set of regions involved in visual processing. These results suggest that abnormal development of visuospatial functional networks in TS may relate to the well documented cognitive difficulties in this disorder. Hum Brain Mapp 34:3117–3128, 2013. © 2012 Wiley Periodicals, Inc.